2022
DOI: 10.1016/j.diagmicrobio.2021.115558
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of respiratory bacterial co-infection in hospitalized COVID-19 patients

Abstract: The primary objectives were to determine the prevalence of and identify variables associated with respiratory bacterial co-infection in COVID-19 inpatients. Secondary outcomes included length of stay and in-hospital mortality. Eighty-two (11.2%) of 735 COVID-19 inpatients had respiratory bacterial co-infection. Fifty-seven patients met inclusion criteria and were matched to three patients lacking co-infection (N = 228 patients). Patients with co-infection were more likely to receive antibiotics [57 (100%) vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies evaluating whether acute phase reactants are useful as predictors of coinfection in patients with COVID-19. Bolker et al [ 22 ] found that the risk factors for respiratory bacterial coinfection upon hospital admission were nursing home stay, severe COVID-19, and leukocytosis; the other inflammatory markers within 72 h of admission (procalcitonin, CRP, IL-6, and ferritin) were not predictors. Mason et al [ 23 ], in a retrospective cohort study of patients with community-acquired pneumonia and patients with COVID-19, proposed that in COVID-19, the absence of both leukocytosis and an antibiotic-related decrease in C-reactive protein can exclude bacterial coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study showed a 3.2% rate of bacterial co-infections on admission and 6.1% during hospitalization [16]. In a different cohort study, a respiratory bacterial co-infection rate of 11.2% was identified [17]. A systematic review described a bacterial co-infection rate of 8%; however, 72% of patients received empirical antibiotic treatment [18].…”
Section: Discussionmentioning
confidence: 99%